2020
DOI: 10.1101/lm.050807.119
|View full text |Cite
|
Sign up to set email alerts
|

Phasic signaling in the bed nucleus of the stria terminalis during fear learning predicts within- and across-session cued fear expression

Abstract: While results from many past studies have implicated the bed nucleus of the stria terminalis (BNST) in mediating the expression of sustained negative affect, recent studies have highlighted a more complex role for BNST that includes aspects of fear learning in addition to defensive responding. As BNST is thought to encode ambiguous or unpredictable threat, it seems plausible that it may be involved in encoding early cued fear learning, especially immediately following a first tone-shock pairing when the condit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 54 publications
4
7
0
Order By: Relevance
“…Although this type of settings could bias responding toward appetitive valence per se , we note that strong fear responding appeared in control groups expressed in high levels ( Figures 1 , 5 ). Thus, our findings further support the role of BNST in phasic Pavlovian fear (Duvarci et al, 2009 ; Haufler et al, 2013 ; De Bundel et al, 2016 ; Bjorni et al, 2020 ). Whereas, previous studies showed a specific role for the BNST in sustained fear but not in phasic fear to a single CS (Davis et al, 2010 ), recent studies have uncovered a role for the BNST in discriminative phasic fear when another CS (CS-, not associated with the shock) is present during training (Duvarci et al, 2009 ; De Bundel et al, 2016 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although this type of settings could bias responding toward appetitive valence per se , we note that strong fear responding appeared in control groups expressed in high levels ( Figures 1 , 5 ). Thus, our findings further support the role of BNST in phasic Pavlovian fear (Duvarci et al, 2009 ; Haufler et al, 2013 ; De Bundel et al, 2016 ; Bjorni et al, 2020 ). Whereas, previous studies showed a specific role for the BNST in sustained fear but not in phasic fear to a single CS (Davis et al, 2010 ), recent studies have uncovered a role for the BNST in discriminative phasic fear when another CS (CS-, not associated with the shock) is present during training (Duvarci et al, 2009 ; De Bundel et al, 2016 ).…”
Section: Discussionsupporting
confidence: 86%
“…The bed nucleus of the stria terminalis (BNST) constitutes a key relay and integration point (Lebow and Chen, 2016 ; Ch'ng et al, 2018 ) between subcortical limbic structures (e.g., amygdala, hippocampus; Dong et al, 2001 ; Dong and Swanson, 2004 ) and downstream regions [e.g., periaqueductal gray (PAG), paraventricular hypothalamus (PVH; Cullinan et al, 1993 ; Dong and Swanson, 2006 )] that underlies appropriate behavioral responses to emotional stimuli (Herman et al, 2003 ; Johnson et al, 2016 ). Although the BNST plays a critical role in anxiety-like or long-lasting sustained fear behaviors (Walker and Davis, 1997 ; Jennings et al, 2013a ; Kim et al, 2013 ), evidence now indicates a direct role of the BNST in phasic fear states (Duvarci et al, 2009 ; Haufler et al, 2013 ; De Bundel et al, 2016 ; Bjorni et al, 2020 ). Yet, other evidence shows the BNST, mostly its dorsal part (dBNST), can modulate both aversive and rewarding phenotypes (Jennings et al, 2013a ; Kim et al, 2013 ; Giardino et al, 2018 ; Girven et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The BNST, meanwhile, supports learning in the absence of the BLA ( Poulos et al, 2010 ; Zimmerman and Maren, 2011 ), and when a stimulus poorly predicts threat ( Lebow and Chen, 2016 ; Goode et al, 2019 ; Bjorni et al, 2020 ), either because it is distal (e.g., predator odor; Fendt et al, 2003 ; Xu et al, 2012 ; Breitfeld et al, 2015 ; Verma et al, 2018 ; Goode et al, 2020 ), diffuse (e.g., contextual; Sullivan et al, 2004 ; Kalin et al, 2005 ; Duvarci et al, 2009 ; Davis et al, 2010 ; Luyten et al, 2012 ; Jennings et al, 2013 ; c.f. Haufler et al, 2013 ), or temporally ambiguous (e.g., random or sustained; Waddell et al, 2006 ; Walker et al, 2009 ; Hammack et al, 2015 ; Daldrup et al, 2016 ; Goode and Maren, 2017 ; Lange et al, 2017 ) with respect to the US.…”
Section: Discussionmentioning
confidence: 97%
“…One possibility is that ELS may induce heightened basal or stimuli-elicited activity in the BNST in a way that causes ELS mice to exhibit social deficits similar to those induced by BNST activation in non-stressed mice. Failing to find effects of BNST activation on social behavior While the complexity of social behavior necessitates arbitration from a number of brain regions (for reviews see Ko, 2017;Li & Dulac, 2018;Zoicas & Kornhuber, 2019), these findings back an idea that the BNST may integrate sensory with contextual information (Bjorni, Rovero, Yang, Holmes, & Halladay, 2020;Goode & Maren, 2017;Lebow & Chen, 2016)-in this case information related to novel conspecifics-to promote behavior appropriate for the given situation. Appropriate social behavioral responding for rodents may be influenced by a number of situational factors, such as the possibility for mating, predation, or establishment of hierarchy.…”
Section: The Bnst Modulates the Aspects Of Social Interactionsmentioning
confidence: 99%